The ETR System: Regenerative tourism education in rural contexts - Gayosso Mexia, Sonia (Tourism and Hospitality International Journal, 2025)
Rural territories in Latin America have been shaped by development models that often reinforce exclusion and ecological degradation, particularly in the tourism sector. In response to this scenario, this study proposes the design and participatory validation of the ETR System (Regenerative Tourism Education), an educational model grounded in critical pedagogy, territorial approaches, and ecosocial justice. The objective is to build a context-sensitive, community-driven tool for tourism education that strengthens territorial appropriation, mobilizes local knowledge, and supports regenerative alternatives to dominant tourism models. Through participatory action research and critical ethnography, the ETR System was co-designed with rural communities and structured around four key dimensions: Contextualized Learning, Community Participation, Territorial Approach, and Ecosocial Regeneration. These dimensions were validated through collective feedback sessions and visual tools that ensured community engagement. Results demonstrate the model's conceptual strength, cultural relevance, and potential to transform tourism training into a process of territorial revitalization. The ETR System is not a fixed curriculum, but a living framework that evolves with the territory, enabling educational practices rooted in memory, sustainability, and collective agency.